2018
DOI: 10.1111/dom.13182
|View full text |Cite
|
Sign up to set email alerts
|

Use and effectiveness of a fixed‐ratio combination of insulin degludec/liraglutide (IDegLira) in a real‐world population with type 2 diabetes: Results from a European, multicentre, retrospective chart review study

Abstract: AimsTo describe the real‐world use and effectiveness of IDegLira, a fixed‐ratio combination of the basal insulin degludec, and the glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) liraglutide.Materials and MethodsThis European, multicentre, retrospective chart review comprised adults (n = 611) with type 2 diabetes, who started IDegLira ≥6 months before data collection. Clinical characteristics were assessed at baseline (defined as the most recent recording during the 6 months before the first IDegLira prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
61
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 22 publications
14
61
3
Order By: Relevance
“…Previous meta‐analyses of randomized controlled trials (RCTs) have shown a mean reduction of HbA1c of around 0.45% in favour of the insulin/GLP‐1RA combination (combo) as compared with other injectable treatment strategies, with no increased hypoglycaemia and reduced body weight. In addition, the results coming from the expanding real world use of the combo strategies tend to confirm the findings of RCTs …”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous meta‐analyses of randomized controlled trials (RCTs) have shown a mean reduction of HbA1c of around 0.45% in favour of the insulin/GLP‐1RA combination (combo) as compared with other injectable treatment strategies, with no increased hypoglycaemia and reduced body weight. In addition, the results coming from the expanding real world use of the combo strategies tend to confirm the findings of RCTs …”
Section: Introductionmentioning
confidence: 54%
“…In another real world study of 39 599 patients with type 2 diabetes who added insulin to a previous GLP‐1RA treatment, the reduction of HbA1c was 0.55% (4 mmol/mol) at 24 months . Finally, in 611 adults with type 2 diabetes, IDegLira initiation produced, after 6 months, significant reductions of HbA1c (−0.9%) (7 mmol/mol) and mean body weight (−0.7 kg). Interestingly, IDegLira was used as an intensification strategy for patients receiving a broad variety of treatment regimens.…”
Section: Discussionmentioning
confidence: 97%
“…They are also supported by the findings of several previous studies that have examined the effect of the IDegLira FRC in real-world setting. In all of these studies, a substantial and significant [16][17][18][19].…”
Section: Discussionmentioning
confidence: 98%
“…The largest of these studies is the European multicenter retrospective real-world EXTRA study, which included 611 patients from five countries on different baseline treatment regimens [16]. In the EXTRA study, IDegLira use resulted in improved glycemic control across all baseline therapy groups, with a substantial -0.9% overall reduction in HbA 1c (P \ 0.001) after 6 months from the initiation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, with the highest pre‐trial dose (40–50 units), the average dose of IDegLira was ~ 40 units by week 12 and plateaued thereafter. This is in contrast to the end‐of‐study IDegLira dose reported from the EXTRA study, a European, multicentre, retrospective chart review of 611 participants with type 2 diabetes, in which participants had a mean IDegLira dose of 30.2 units at 6 months and mean HbA 1c was 59 mmol/mol (7.5%), from a baseline value of 69 mmol/mol (8.5%) . These results suggest that real‐world outcomes could be further improved with greater focus on titration.…”
Section: Discussionmentioning
confidence: 61%